Risk factors of cerebral palsy in the perinatal period - Santi Gunarwati; S. Yudha Patria; Madarina Julia (Indonesian Pediatric Society Publishing House, 2016)
Background Cerebral palsy is an irreversible yet preventable condition, thus it is necessary to know the risk factors of the disease. The potential risk factors that are found in the perinatal and neonatal period i.e. asphyxia, sepsis, very low birth weight, premature birth, and neonatal seizure. No available data for the risk factors of cerebral palsy in Indonesia. Objective To identify the perinatal risk factors in cerebral palsy. Methods We performed an age and sex-matched nested case- control study. The case group was children with cerebral palsy who were born at Sardjito Hospital during 1997-2005. The control group was selected from the same population as the case group. Risk factors during the perinatal period consisted of asphyxia, sepsis, very low birth weight, premature birth and neonatal seizure. Logistic regression was used to determine the association between risk factors and cerebral palsy. Results Univariate analysis showed that the following factors were risk factors for cerebral palsy, i.e., asphyxia (OR 5.6, 95%CI 2.48; 12.53); premature birth (OR 4.5; 95%CI 1.55; 13.13); and neona- tal seizure (OR 7.5, 95%CI 3.13; 18.03). On multivariate analysis risk factors associated with cerebral palsy were asphyxia (aOR 6.3, 95%CI 2.42; 16.66) and neonatal seizure (aOR 10.9,95%CI 4.03; 29.97). Conclusion Asphyxia and neonatal seizure are significant risk factors of cerebral palsy in perinatal period